Graph Solver as a Service - Ahmad, Fozail (Proceedings (IEEE/ACM International Conference on Software Engineering Companion. Online), 2023)
Graphs can be a key abstraction for formal verifi-cation challenges. As such, graph solvers are essential tools for synthesizing scalable domain-specific consistent graph models, which are both realistic and diverse. The main goal of this doctoral research plan is to develop a graph solver framework based on a state-of-the-art graph solver in order to provide a graph solver as a service. We expect this will improve the overall scalability of graph solvers whilst increasing the usage and adoption of such tools. The scalability of the framework will be investigated in several case studies of different complexity.